Mono and combination therapies in pulmonary arterial hypertension patients with comorbidities: a COMPERA analysis - Skowasch, Dirk; Pausch, Christine; Huscher, Doerte; Pittrow, David; Wede, Judith; Kreimendahl, Fabian; Rosenkranz, Stephan; Beckmann, Stephan; Held, Matthias; Grünig, Ekkehard; Ghofrani, H. Ardeschir; Klose, Hans; et al. (ESC heart failure, 2025)
Aims Pulmonary arterial hypertension (PAH) is often diagnosed in elderly patients with comorbidities. Although initial monotherapy is recommended for these patients, the value of combination therapy remains unclear. Here, we compare the efficacy of initial monotherapy and combination therapy in PAH patients with cardiovascular comorbidities. Methods and results Data from adult patients with incident pre-capillary PAH and cardiovascular comorbidities from the COMPERA database (European registry for PH) were analysed. A matched-pair analysis of patients treated with monotherapy versus combination therapy based on age, sex, WHO functional class (FC) and 4-strata risk at baseline was performed. The matching strategy identified 216 pairs of PAH patients with cardiovascular comorbidities, who differed considerably from the enrolled patient population (n = 1871), especially in terms of mean age (mono: matched pairs 62.9 ± 13.5 years vs. 70.6 ± 11.4 years, combination: matched pairs 62.0 ± 13.6 years vs. 60.5 ± 14.9 years). In the matched-pair analysis, the initial combination therapy group showed more pronounced improvements in WHO-FC, N-terminal pro-B-type natriuretic peptide (BNP/NT-proBNP) and risk status than patients treated with initial monotherapy, with no significant differences in 6-min walk distance (6MWD), PAH-related hospitalisations, survival and drug discontinuation. Conclusions This analysis suggests that PAH patients with comorbidities may benefit more pronounced from combination therapy regarding WHO-FC, BNP/NT-pro-BNP and risk status without a significant difference in survival. Good tolerability is indicated. However, given the relatively younger patient matched subgroup, these findings may not necessarily apply to older patients with a wider range of comorbidities.
Veröffentlicht: 04 March 2025
Gesehen am 15.09.2025